Centralized Versus Decentralized Resource Allocation: The Yugoslav "Laboratory" - Marschak, Thomas A. (Quarterly Journal of Economics, 1968)
I. Introduction: comparing allocation mechanisms in an ideal laboratory, 561. — II. The "administrative" period in postwar Yugoslavia, 567. — III. The decentralized mechanism in Yugoslavia, 572. — IV. The administrative and the decentralized periods: comparison of aggregates, 574. — V. The performance of the new mechanism: noncomparative analysis, 579. — VI. Concluding remarks, 585.